Incorporating Atmospheric Stability Effects into the FLORIS Engineering Model of Wakes in Wind Farms. Issue 5 (September 2016) - Gebraad, P. M. O.; Churchfield, M. J.; Fleming, P. A.
Abstract: Atmospheric stability conditions have an effect on wind turbine wakes. This is an important factor in wind farms in which the wake properties affect the performance of downstream turbines. In the stable atmosphere, wind direction shear has a lateral skewing effect on the wakes. In this paper, we describe changes to the FLOw Redirection and Induction in Steady-state (FLORIS) wake engineering model to incorporate and parameterize this effect.